Defining the target and the effect of imatinib on the filarial c-Abl homologue - O’Connell, Elise M. (PLoS Negl Trop Dis, 2017)
BACKGROUND: Previously we demonstrated the micro- and macrofilaricidal properties of imatinib in vitro. Here we use electron and multiphoton microscopy to define the target of imatinib in the adult and microfilarial stages of Brugia malayi and assess the effects of pharmacologically relevant levels of imatinib on the adult parasites. METHODS: After fixation of adult B. malayi males and females, sections were stained with polyclonal rabbit anti-c-Abl antibody (or isotype control) and imaged with multiphoton fluorescent microscopy. Microfilariae were fixed and labeled with rabbit anti-c-Abl IgG primary antibody followed by anti-rabbit gold conjugated secondary antibody and imaged using transmission electron microscopy (TEM; immunoEM). In addition, adult B. malayi males and females were exposed to 0 or 10μM of imatinib for 7 days following which they were prepared for transmission electron microscopy (TEM) to assess the drug’s effect on filarial ultrastructure. RESULTS: Fluorescent localization of anti-c-Abl antibody demonstrated widespread uptake in the adult filariae, but the most intense signal was seen in the reproductive organs, muscle, and intestine of both male and female worms. Fluorescence was significantly more intense in the early microfilarial stage (i.e. early morula) compared with later development stages (i.e. pretzel). Anti-c-Abl antibody in the microfilariae localized to the nuclei. Based on TEM assessment following imatinib exposure, imatinib appeared to be detrimental to embryogenesis in the adult female B. malayi. CONCLUSIONS: At pharmacologically achievable concentrations of imatinib, embryogenesis is impaired and possibly halted in adult filariae. Imatinib is likely a slow microfilaricide due to interference in intra-nuclear processes, which are slowly detrimental to the parasite and not immediately lethal, and thus may be used to lower the levels of L. loa microfilariae before they are treated within the context of conventional mass drug administration.